2020
DOI: 10.1101/2020.12.08.20245886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends in Phase II trials for cancer therapies

Abstract: BackgroundDrug combinations are the standard of care in cancer treatment. Identifying effective cancer drug combinations has become more challenging because of the increasing number of drugs. However, a substantial number of cancer drugs stumble at Phase III clinical trials despite exhibiting favourable efficacy in the earlier Phase.MethodsWe analysed recent Phase II cancer trials comprising 2,165 response rates to uncover trends in cancer therapies and used a null model of non-interacting agents to infer syne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…We did not compare the response rates between single-drug and multiple-drug studies because the majority of trials in our sample were single-drug studies. Previous studies have shown that using a combination of a few agents increases the likelihood of benefiting in a trial [ 17 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not compare the response rates between single-drug and multiple-drug studies because the majority of trials in our sample were single-drug studies. Previous studies have shown that using a combination of a few agents increases the likelihood of benefiting in a trial [ 17 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination provides a potential treatment for combating SARS-CoV-2, which can hardly be treated by any single drug. However, drug combinations can also be harmful without precise medicine [10,11]. Therefore, it is pretty important to accurately find synergistic drug pairs for a cell type in case we want to take advantage of drug combination therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Lapatinib or Rapamycin alone has little therapeutic effect, but their combined treatment has been reported to significantly increase the apoptosis rate of triple-negative breast cancer cells (Liu et al, 2011). However, some drug combinations may cause antagonistic effect and even aggravate the disease (Azam and Vazquez, 2021). Therefore, it is crucial to accurately discover synergistic drug combinations to specific diseases.…”
Section: Introductionmentioning
confidence: 99%